2022
DOI: 10.3389/fmed.2021.800040
|View full text |Cite
|
Sign up to set email alerts
|

Relief After COVID-19 Vaccination: A Doubtful or Evident Outcome?

Abstract: Background: Since development of the first COVID-19 vaccine, the landscape of public confidence in these vaccines is uncertain. Building confidence is crucial for better preparedness of future pandemics. Following the mandatory COVID-19 vaccination policy in the country, the aim of this study was to examine whether the Saudi public feels relieved post-vaccination and to identify the factors predicting such relief.Methods: An online cross-sectional survey was conducted in July 2021 among COVID-19 vaccine recipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…One plausible explanation for these trends could be the extended time families spent together during lockdowns, providing opportunities for bonding, understanding, and mutual support. Nevertheless, previous studies showed that people's well-being improved with the foreseeing end of the pandemic, and even more so after vaccination programs commenced [31,32].…”
Section: Literature Analysismentioning
confidence: 98%
“…One plausible explanation for these trends could be the extended time families spent together during lockdowns, providing opportunities for bonding, understanding, and mutual support. Nevertheless, previous studies showed that people's well-being improved with the foreseeing end of the pandemic, and even more so after vaccination programs commenced [31,32].…”
Section: Literature Analysismentioning
confidence: 98%
“…Earlier experience with COVID 19 shows that heterologous vaccine programs utilizing vaccines from different platforms to augment vaccine-induced immunity are highly warranted to stimulate robust immunity which could eventually prevent viral infection and its transmission [9] . However, public confidence in vaccines should be reinforced [10] . The following research questions need to be addressed: How vaccines can and should be used, safety data, Cost, vaccine delivery strategies, and duration of vaccine effect.…”
mentioning
confidence: 99%